Prevalence and factors associated with auditory dysfunction in prematures infant of very low birth weight in the INMP. 2009-2011 - Morillo Acuña, María Mercedes (2014)
Objetives. To determine the prevalence and the main factors associated with auditory dysfunction in prematures infant of very low weight attended at birth from October 2009 to December 2010. Material and methods. Prospective analytical study. It include all prematures infant of very low weight at birth admitted to the INMP from October 2009 to December 2011. Prior clinical evaluation it applied emissions testing otoacoustic prior to hospital discharge or 30 days of postnatal age 3 months of corrected age, during follow-up. Results. It was found a prevalence of hearing loss in 9.2/1000 RNMBP; 30 patients were with uncertain outcome in the firts examination of EOA because of desertion to the control. Conclusions. The prevalence of auditory dysfunction in prematures infant of very low weight at birth in our environment was hight (9.2/1000), matches in the literature, it is necessary to perform a programme of universal newborn hearing screening in this population of the INMP due to the consequences social and in the neurodevelopment.